THE MAIN FACTORS THAT LEAD TO THE NON PARTICIPATION OF THE STUDENTS ON PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2014)
The object of study of this monograph is the reflection on the school Physical Education: how it has been applied on high school grades, and why the classes don't often awaken practical interest of the students. This work had the objective of identifying the origins and the reasons why the students move from the practice of physical activity on school Physical Education. The study was based on a descriptive research and was performed through a questionnaire with a unique and closed question. The chosen group was composed of 30 students who were coursing from 1st to 3rd grade of high school with ages from 15 to 27 years old. This work meant to look for the main factors which lead to the lack of interest of the students for the Physics Education classes. The results show that the most cited factor, with 23,3% of votes was the “laziness”, followed by “I don't have abilities”, with 20,0% of the students, and “I don't like physical activity” with 11,1%. It was possible to identify with this study, that there are other factors which influence in the participation of the students on physical education classes, and the teacher in possession of these information must re-examine his planning of class, and also his attitudes as an educator, in order to awaken the interest of the students, decreasing this way, the escape of the physical education classes.
Keywords: disinterest; students; Physics Education